Postural Balance Ability and the Effect of Visual Restriction on Older Dancers and Non-Dancers - Nikolaidou, Maria-Elissavet; Karfis, Vasilios; Koutsouba, Maria; Schroll, Arno; Arampatzis, Adamantios (Frontiers in Sports and Active Living, 2021)
Dance has been suggested to be an advantageous exercise modality for improving postural balance performance and reducing the risk of falls in the older population. The main purpose of this study was to investigate whether visual restriction impacts older dancers and non-dancers differently during a quiet stance balance performance test. We hypothesized higher balance performance and greater balance deterioration due to visual restriction in dancers compared with non-dancers, indicating the superior contribution of the visual channel in the expected higher balance performances of dancers. Sixty-nine (38 men, 31 women, 74 ± 6 years) healthy older adults participated and were grouped into a Greek traditional dance group (n = 31, two to three times/week for 1.5 h/session, minimum of 3 years) and a non-dancer control group (n = 38, no systematic exercise history). The participants completed an assessment of one-legged quiet stance trials using both left and right legs and with eyes open while standing barefoot on a force plate (Wii, A/D converter, 1,000 Hz; Biovision) and two-legged trials with both eyes open and closed. The possible differences in the anthropometric and one-legged balance parameters were examined by a univariate ANOVA with group and sex as fixed factors. This ANOVA was performed using the same fixed factors and vision as the repeated measures factor for the two-legged balance parameters. In the one-legged task, the dance group showed significantly lower values in anteroposterior and mediolateral sway amplitudes (p = 0.001 and p = 0.035) and path length measured in both directions (p = 0.001) compared with the non-dancers. In the two-legged stance, we found a significant vision effect on path length (p < 0.001) and anteroposterior amplitude (p < 0.001), whereas mediolateral amplitude did not differ significantly (p = 0.439) between closed and open eyes. The dance group had a significantly lower CoP path length (p = 0.006) and anteroposterior (p = 0.001) and mediolateral sway amplitudes (p = 0.003) both in the eyes-open and eyes-closed trials compared with the control group. The superior balance performance in the two postural tasks found in the dancers is possibly the result of the coordinated, aesthetically oriented intersegmental movements, including alternations between one- and two-legged stance phases, that comes with dance. Visual restriction resulted in a similar deterioration of balance performance in both groups, thus suggesting that the contribution of the visual channel alone cannot explain the superior balance performance of dancers.